2002
DOI: 10.1117/12.475687
|View full text |Cite
|
Sign up to set email alerts
|

<title>Exact computation of scalar 2D aerial imagery</title>

Abstract: An exact formulation of the problem of imaging a 2D object through a Köhler illumination system is presented; the accurate simulation of a real layout is then not time-limited, but memory-limited. The main idea behind the algorithm is that the boundary of the region that comprise a typical TCC is made up of circular arcs, and therefore the area -which determines the value of the TCC -should be exactly computable in terms of elementary analytical functions. A change to integration around the boundary leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The approach taken in the current study is to find closed-form solutions from the research literature, and to use these solutions as an absolute standard for benchmarking lithography simulators. This is similar to the approach taken by Brunner [2] and Gordon [3].…”
Section: Introductionsupporting
confidence: 54%
“…The approach taken in the current study is to find closed-form solutions from the research literature, and to use these solutions as an absolute standard for benchmarking lithography simulators. This is similar to the approach taken by Brunner [2] and Gordon [3].…”
Section: Introductionsupporting
confidence: 54%
“…(8), and it is equal to or larger than (1 þ r) in optical lithography with the partial coherence factor of the source being r; N ¼ (2 N A þ 1)N R is the total number of CSFs with angle factor n from ÀN A to N A and radial factor s from 1 to N R ; u k (aq, h) stands for the kth CSF; and p k,l are the expansion coefficients. (8), and it is equal to or larger than (1 þ r) in optical lithography with the partial coherence factor of the source being r; N ¼ (2 N A þ 1)N R is the total number of CSFs with angle factor n from ÀN A to N A and radial factor s from 1 to N R ; u k (aq, h) stands for the kth CSF; and p k,l are the expansion coefficients.…”
Section: Theorymentioning
confidence: 99%
“…Further, it has been shown that the number of TCCs varies as the square of the area of the periodic unit cell, 10 it is clear that for larger areas, the numerical method becomes unwieldy.…”
Section: Illustration Of the Theorymentioning
confidence: 99%